Híbridos e espécies de pínus com potencial para produção de madeira e resina - Menucelli, João Roberto (Universidade Federal de São Carlos, 2024)
This study aimed to evaluate the potential of pine species and interspecific hybrids for wood and resin production. In 2013, a test of hybrids and pure pine species was implemented in the Pederneiras State Forest. The species used were: P. elliottii var. elliottii, P. caribaea var. hondurensis, P. caribaea var. bahamensis. The hybrids were: P. elliottii var. elliottii x P. caribaea var. hondurensis and P. elliottii var. elliottii x P. caribaea var. bahamensis. A randomized complete block experimental design was adopted with five treatments, three blocks of each treatment with 189 seedlings, for a total of 567 per treatment. The spacing used was 3.5 x 3.0 meters. At six years of age, the following traits were measured: diameter at breast height (DBH-cm) and total height (H-m), and individual volume (VOL-m³/arv). At seven years of age, the resin flow potential (RSN-g) was measured through microresination. The descriptive analysis was performed using the SELEGEN software. The analysis of variance was performed according to the REML/BLUP procedure in the R software. A significant difference at the 1% level was detected between treatments, only for height and DBH. The mean values (minimum to maximum) for height, DBH and resin flow were: 8 m (2 to 15.70 m), 13 cm (0.95 to 26.42 cm) and 0.50 g, (0.01 to 17.01 g), respectively. The correlations between the growth traits were high and significant, and for resin flow they were low and not significant. The observed phenotypic variation indicates that the hybrid between P. elliottii var. elliottii x P. caribaea var. bahamensis presented the best results and could generate significant gains for wood and resin production through the selection of individuals to compose commercial populations or pine genetic improvement trials.
Hybrids and pine species with potential for wood and resin production
Keywords: Madeira; Hibridação; Qualidade da Madeira; Hybridization; Wood; Wood Quality; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL